An Overview of Quality of Nursing Work-Life In The Inpatient Ward - Fioren, Gabriela; Mustamu, Nathania Aurelya; Sahertian, Viona Fransin; Patrisia, Ineke; Pramusita, Santa Maya (Universitas Airlangga, 2024)
Introduction: Quality of nursing work life (QNWL) is the satisfaction of nurses with personal and organizational life, which is gained through working experience to achieve organizational goals. Low QNWL might result in a high willingness to move to another ward or other departments. This study aimed to identify the dimension and quality of nursing work life in the inpatient ward. Methods: This study was quantitative descriptive, and the population in this study were nurses who worked in the inpatient ward, as much 146 respondents. Total sampling technique used in this study. The data were self-reported and analyzed using univariate tests. Results: The results also showed that most respondents (96.6%) had a good quality of nursing work life. The dimensions of work life/ home life have a good category (97.9% of respondents). Most of the work design dimension respondents are in a good category (79.7% of respondents). In the work context dimension, almost all respondents were in a good category as much as 97.9%. Meanwhile, in the work world dimension, 85.6% of respondents were in the good category. Conclusions: The results of the study obtained an overview of the QNWL in a private hospital in western Indonesia. Almost all respondents reported the QNWL was in a good category. This study underlines the highest dimension of QNWL, the strongest impact on job satisfaction. Future researchers can identify the quality of work life of nurses in a wider scope in other clinical settings.